131k views
5 votes
Divide: (x2 – 3x – 33) = (x + 4)

Divide: (x2 – 3x – 33) = (x + 4)-example-1
User Isso
by
4.5k points

2 Answers

3 votes

Answer:


\rm (x^2 - 3x - 33)/(x + 4) = x - 7 - (5)/(x + 4)

Explanation:


\rm\qquad\quad\quad{x-7}\\ \begin{array}{cc} \cline{2 - 2}\rm x + 4 )&\rm \ x^2 - 3x -33\\&\rm x^2 + 4x \\ \cline{2-2}& \rm \ \ \ \ -7x-33\\ &\sf \ - 7x-28 \\ \cline{2-2} & \rm \ \ -5 \\ \cline{2-2} \end{array}

Quotient → x - 7

Remainder → -5

Divisor → x + 4

User Lgargantini
by
4.4k points
3 votes

Answer:

x-7-5/x+4

So answer C

Explanation:

User Gavriguy
by
5.3k points